Hubungan Dukungan Orang Tua dengan Kecemasan pada Mahasiswa Fakultas Keguruan dan Ilmu Pendidikan Universitas Sultan Ageng Tirtayasa Angkatan 2017 yang Sedang Menyusun Skripsi - Nurul Dwi Asrifa (Jurnal al-Shifa Bimbingan Konseling Islam, 2021)
Anxiety can occur in final year students when writing a thesis. Some of the demands experienced by students cause them to be anxious, stressed, and depressed. Family is one of the factors that have a risk for the occurrence of anxiety in individuals. Children need parental support as motivation and reduce anxiety that occurs. Students who get support will get positive scores in completing their thesis, are confident, have self-esteem, and relatively low anxiety. This study aims to determine the relationship between parental support and anxiety in students. The population in this study were students of class 2017 or semester VIII of the Faculty of Teacher Training and Education, University of Sultan Ageng Tirtayasa who were preparing a thesis. The sampling technique used a proportional sampling technique, a lottery system with the slovin formula which resulted in a sample of 288 students. Data analysis using correlation analysis using SPSS 16.0 for windows. Correlation test results obtained R = -0.436, P = 0.000 (P <0.05). So it can be concluded that the parental support variable has a significantly negative relationship with anxiety.